Actions to inhibit environmental impacts on clandestine landfills in the Amazon - Oliveira, Maria do Perpétuo Socorro Lamego (2021)
This research studies the negative environmental impacts of clandestine landfills in the Amazon, caused by the illegal disposal of construction waste. In the city of Manaus, located in the center of the Amazon, Brazil, there is a public landfill comprising a solid waste collection complex with an area of 660,000.00 m2. In 2018, this landfill received approximately 932,927.00 t of solid urban waste, an average of 2,537.20 t/day. Unfortunately, less than 1% of this waste was destined for valorization (0.92% were for composting, and 0.05% were recycled). This legalized public landfill does not accept the disposal of construction and demolition waste, claiming the decrease in the lifetime of the landfill. However, this regional public policy prohibiting the disposal of construction and demolition waste in public landfills favors the use of clandestine landfills with harmful effects on the environment of the Amazon. This research presents proposals for actions to validate a mobile phone application with the authorities responsible for the Manaus landfill for recycling construction waste, with the aim of stimulating the circular economy and inhibiting the negative environmental impacts of illegal clandestine landfills.